Association of Myocardial Perfusion and Coronary Flow Reserve with Prognosis in Patients with Aortic Stenosis: Systematic Review and Meta-Analysis - Saadia Aslam; Muhammad Haris; Keith Nockels; Amitha Puranik; Srdjan Aleksandric; Marko Banovic; Gerry P. McCann; Anvesha Singh (Hearts, 2024)
Background: Coronary microvascular disease is associated with adverse prognosis in a range of cardiovascular diseases, but its prognostic role in patients with aortic stenosis (AS) is unclear. The aim of this systematic review and meta-analysis is to determine the prognostic role of myocardial perfusion and coronary flow reserve, assessed using non-invasive imaging modalities, in patients with AS. Methods: We conducted a systematic review and meta-analysis of all studies assessing myocardial perfusion reserve (MPR) or coronary flow reserve (CFR) in patients with AS and reporting clinical outcomes, from inception to January 2024. The definition of abnormal MPR/CFR and major adverse cardiovascular events (MACE) was that used in each study. Estimates of effect were calculated from hazard ratios (HRs) and 95% confidence intervals (CIs) using a random-effects model. Results: Four studies comprising 384 participants met the inclusion criteria. Myocardial/coronary blood flow was assessed using Doppler echocardiography (n = 2), PET (n = 1), or cardiac magnetic resonance (n = 1). The median optimal cutoff for MPR/CFR across all studies was 2.01 (range 1.85–2.13), with 109 events. Impaired MPR/CFR was associated with a higher incidence of MACE (HR 3.67, 95% CI: 1.66, 8.09, I2 = 63%) in the overall population. Conclusions: Reduced MPR/CFR is associated with increased risk of MACE in patients with AS, although significant heterogeneity exists in published studies. Further studies are required to establish its role in the risk stratification of asymptomatic patients with AS.